2021
DOI: 10.1021/acs.est.0c07603
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Persistent Toxic Substances in Protective Cases of Mobile Phones: Occurrence, Health Risks, and Implications

Abstract: Despite the popularity of smartphones worldwide, persistent toxic substances (PTSs) in protective cases of mobile phones (PCMPs) and their health risks via direct skin contact have been ignored. This study investigated PTSs in PCMPs made in China with different materials and sales territory and their potential harm to human health. Polybrominated diphenyl ethers (PBDEs, 6.40 ng/g), new brominated flame retardants (NBFRs, 144 ng/g), organophosphate esters (OPEs, 10.1 μg/g), short-chain chlorinated paraffins (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…[ 19 ] Data from various studies suggest that substances from naturally derived, principally flavonoids, have a central role in the improvement of learning, and memory performance. [ 20 ] A favorable influence of quercetin on memory and cognitive functions has also been reported. [ 21,22 ] The results of the present study showed the novel beneficial effects of quercetin in attenuating memory and cognitive impairments and loss of dopaminergic fibrous, reduced number of degenerative neurons in the hippocampus, and inhibition of neuroinflammation in mice brains.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Data from various studies suggest that substances from naturally derived, principally flavonoids, have a central role in the improvement of learning, and memory performance. [ 20 ] A favorable influence of quercetin on memory and cognitive functions has also been reported. [ 21,22 ] The results of the present study showed the novel beneficial effects of quercetin in attenuating memory and cognitive impairments and loss of dopaminergic fibrous, reduced number of degenerative neurons in the hippocampus, and inhibition of neuroinflammation in mice brains.…”
Section: Discussionmentioning
confidence: 99%